Unraveling the Radiation Damage of n-dodecanetiol Self-Assembled Monolayers on Au(100) and Au(111): a Prerequisite to Understand the Oriented-Attachment of Au Nanoparticles - Aagaard, Natalia Desiré; Zelaya, Maria Eugenia; Fonticelli, Mariano Hernan; Azcárate, Julio César (American Chemical Society, 2021)
Fil: Aagaard, Natalia Desiré. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina